'The poor are not us!': an exploration into the transforming possibilities of Old Testament and African proverbs on poverty - Kimilike, Lechion Peter (Old Testament essays, 2006)
The phrase 'the poor are not us' captures the socio-economic transforming framework held by ordinary people in Africa in the challenge of poverty. It is a dynamic paradigm that expresses positive nationalism and promotes a welfare economy to secure life in society. This African heritage can be used by readers of the Bible, regardless of status, to work at a meaningful interpretation in the struggle against poverty today. The article presupposes a similar holistic world view of ancient Israel informing the poverty proverbs. It situates the latter in a popular social context thus emphasizing a holistic transforming perspective of poverty proverbs in the Book of Proverbs